Power, Culture and Situated Research Methodology - Neumann, Cecilie Basberg. author. aut Link
VII, 115 p.
Keywords: This book explores the extent to which our lives become an important underlying context for data production. Drawing on insights from Gestalt psychology, feminism and post-structuralism, it discusses how to situate yourself in the different phases of research.